An Improvement in Maximum Difference Method to Find Initial Basic Feasible Solution for Transportation Problem - kaur, Lakhveer; Rakshit, Madhuchanda; Singh, Sandeep (International Journal of Computer Sciences and Engineering, 2018)
It is very important to find initial solution of transportation problems to reach optimal solution. In this paper Maximum Difference Method (MDM) is improved to get best initial solution of transportation problems. Our improved method overcomes the limitations of MDM given by Smita Sood and keerti Jain. This modified approach most of times give better solution than MDM specially in case of tie and very close to the optimal solution. Also sometimes gives optimal solution.